Climate Smart Cocoa in Côte d’Ivoire Towards climate resilient production at scale - Bunn, Christian; Fernández Kolb, Pablo; Lundy, Mark M. (2019)
Climate Smart Cocoa (CSC) furthers the objectives of Climate Smart Agriculture in cocoa production. These objectives are: increasing productivity and improving farmers livelihoods, adaptation to climate change, and mitigation of greenhouse gas emissions. Current cocoa production practices in Côte d’Ivoire still have a long way to improve toward greater resilience and achieving CSA goals. Cocoa farms in Côte d’Ivoire are vulnerable to an array of climate-related risks: the Harmattan wind, droughts, storms, flooding. Climate change is projected to increase the occurrence of such extreme events, as well as induce more gradual changes to cocoa farming suitability via higher average temperatures and more erratic rainfall. Whether sudden or gradual, production needs to be resilient to these changes.